Determinants of Longevity: Genetics, Biomarkers and Therapeutic Approaches - Jylhava, Juulia (Current Pharmaceutical Design, 2014)
Our understanding of the determinants of human life span and longevity has increased markedly during the last few decades. A number of environmental, lifestyle and genetic factors associated with longevity have been identified, and the intricate interplay between these components has been recognized. Various therapeutic approaches, especially those at the somatotropic and immunological axes, have been presented as means to reverse some of the impairments that accompany the aging process. Nevertheless, a considerable level of unexplained interindividual variation exists in the human life span, and despite promising results in animal models, many of the rejuvenation trials in humans have yet to be successful. This review discusses the genetic component of human longevity and its phenotypic effectors: the biomarkers and their target pathways. The focus is set on the somatotropic and immunological axes. In addition, a new longevity biomarker candidate, a circulating cell-free DNA (cf-DNA), is presented. cf-DNA is unique in that virtually any dying or senescent cell type can release it, making it a sensitive and compelling biomarker for aging research. Lastly, this review discusses several of the rejuvenation strategies proposed to augment senescent phenotypes. Because there is a growing interest in personalized treatment modalities and risk prediction scores in various age-related disorders, we highlight some of the genetic and age- and sex-specific factors that can modulate the response to such interventions.
Keywords: biomarker